Determinan Harga Saham Pertambangan di Indonesia - Adni Dwi Astuti; Moh Syaiful Anwar (Al-Tijary, 2019)
The purpose of this research is to know the influence of profitability, solvency, and commodity prices on the stock price of mining companies listed on the Indonesia Stock Exchange (IDX) in 2008-2018. Some aspects used in research include financial ratios such as ROE (Return of Equity), EPS (Earning per share of common stock) for variable profitability and DER (Debt to Equity Ratio) for solvency as well as the addition of external factors Like commodity prices to see how it affects the price of the stock. This research is conducted by the documentation method using data from the financial report of the mining company obtained from the Indonesia Stock Exchange website. The analytical methods used in the research are the classical assumption test analysis and the data regression panel. This research uses a data mining company registered in Jakarta Islamic Index (JII) in 2008 – 2018 as 5 companies from 27 registered companies. The results of the Common-Constant estimation method (Pooled Ordinary Least Square/PLS) found that DER and EPS influence the stock price of the mining company partially, While commodity prices do not have a significant effect against the stock price of mining companies. ROE, DER, EPS and commodity prices do not have a significant effect on the stock price of mining companies, it can be demonstrated by the R-Squared 0.150565 value which means the above variables affect only 15.05% and the remaining 84.95% is determined by other variables not researched in this study.